Connotation Composition and Cultivation Pathways of Digital Literacy for Preschool Education Teacher Trainees: Based on the “Teacher Digital Literacy” Standard - Li, Renjie (Journal of Educational Research and Policies, 2025)
Following the promulgation of the “Teacher Digital Literacy” standard in 2022, the preschool education field faces a disconnect between universal standards and micro-level practices due to characteristics such as the concrete nature of young children’s cognition, the unique task of integrated care and education, and heightened sensitivity to ethics and safety. This paper, based on this standard and integrating the three core characteristics of preschool education, constructs a digital literacy framework for preschool teacher trainees and designs cultivation pathways. Regarding connotation composition, five core competencies are formed: Understanding of Digital Transformation in Care and Education, requiring the establishment of a dialectical view of technology value and vigilance against technology’s negative impact on teacher-child interaction; Appropriate Technological Operational Competence, focusing on normative, age-appropriate tool operation in scenarios like behavior observation and environment creation; Integrated Care and Education Competency, translating standards into practical care and education activities like AR game design and wearable device applications; Child Safety Safeguarding Capability, implementing stricter standards for privacy, health, and content protection; and Technology-Enabled Reflective Capacity, utilizing intelligent teaching-research tools for data-driven professional reflection. In terms of cultivation pathways: the goal system is made concrete, setting observable indicators like designing mixed reality games; the curriculum system adopts a dual-track strategy of “transformation courses + disciplinary integration,” developing prerequisite courses like ethics and gamification design while revamping core courses; the teaching model uses PBL contextualized projects as an engine to foster technological decision-making ability; practice evaluation employs dual-mentor collaborative rubrics, with ethical compliance as a one-vote veto item. This research achieves a creative integration of national standards with preschool practice, aiding teacher trainees’ qualitative transformation from “technology users” to “digital educators.”